Injection time related to intraocular pressure using a CO2 driven preloaded injector: An experimental laboratory study. - Jan N Weindler (Public Library of Science (PLoS), 2021)
Purpose Experimental study to measure the intraocular lens (IOL) injection time and injection speed at different intraocular pressure (IOP) settings when using the AutonoMe® injector. Methods In this experimental study, following phacoemulsification in porcine cadaver eyes, a trocar was inserted at pars plana with a connected infusion and IOPs of 20, 50 and 80 mmHg were generated by altering the infusion height. Twelve CO2 gas-driven injectors were used to implant an IOL via a corneal incision of 2.2 mm. For each IOP setting, the duration of the IOL injection and the injection speed was measured by analyzing a video recording of the procedure. Results The mean ±SD injection time (seconds) was 4.47±0.50 at 20 mmHg, 4.98±0.55 at 50 mmHg and 5.47±0.20 at 80 mmHg. The mean ±SD injection speed (millimeters per seconds) was 1.36±0.15 at 20 mmHg, 1.22±0.14 at 50 mmHg and 1.10±0.04 at 80 mmHg. There was a significant (p<0.05) difference between the 20 and 80 mmHg groups in mean injection duration and injection speed. Conclusion The CO2 gas driven injector allows a safe IOL injection even at elevated IOP. Although the implantation time is slightly extended at higher IOPs, this does not seem to be clinically relevant. No IOL damage was observed at these pressure settings.